Evaluation of fodder yield and fodder quality in sorghum and its interaction with grain yield under different water availability regimes - Somegowda, V.K.; Vemula, A.; Naravulab, J.; Prasad, G.; Rayaprolu, L.; Rathore, A.; Blümmel, Michael; Deshpande S.P. (Elsevier, 2021)
Sorghum is widely grown as a failsafe crop in semi-arid regions particularly in post rainy season. Though the effect of drought on crop performance is studied widely there are few studies illustrating the association of fodder quality and agronomic traits under drought. To study the interactions we evaluated a set of 24 cultivars under drought for three years in post rainy season. The effect of drought was evident in delayed flowering (by 2 days) and reduce plant height (by 0.98 cm) compared to control. The fodder digestibility traits were reduced (in vitro organic matter digestibility by 2.25 times) under drought. All the plant growth and yield parameters recorded higher heritability compared to fodder quality parameters (<0.75) in most of the season in both control and stress environments. The scatter plot showed best (ICSV700-P10, N13, PB15881-3, SP 2417-P3) and poor (296B, ICSB377-P1, ICSV1, IS9830) performing entries in control and stress plots. The agronomic and the fodder quality traits have shown no significant relationship between them, hence independent association can be utilized to breed for desirable traits. Identification of contrasting lines could be the key to identify genes controlling the fodder quality traits under drought.